The level of awareness and application of energy-efficient strategies in landed residences of Melaka suburban / Nurul Atikah Zolkarnain ... [et al.] - Zolkarnain, Nurul Atikah; Ali Ariff, Azlan Ariff; Abdul Jalil, Nurul Amira; Abdul Apet, Rabiatul Adawiyyah (2022)
Population dynamics due to urban sprawl are one of the environmental consequences since population expansion in the city and changing lifestyles have affected energy supply demand in suburban areas, resulting in a growing conflict of energy consumption. The application of renewable energy (RE) and energy-efficient strategies is vital for environmental sustainability in residential buildings. This research aims to establish the importance of adopting energy-efficient and renewable energy onto residential buildings in monitoring carbon footprint due to urban sprawl. The objective is to investigate the level of awareness and application of energy-efficient strategies in landed residences of the Melaka suburban area and how these strategies contribute towards energy efficiency to meet the future energy demand. The questionnaire included various questions to provide an understanding of the residents’ level of awareness towards the application of energy-efficient strategies in residential buildings and their actual implementations, such as the use of solar panels. Three different types of landed residential buildings in Taman Angsa Mas and Taman Kasawari were chosen to collect the building temperature data and assess the application of energy-efficient strategies among the residents. The result shows that the residents are aware of the importance of energy efficiency, supported by the finding that residential house integrated with solar panel has the lowest mean room temperature. This is due to the mechanism of solar panels, which preclude heat from being absorbed by the roof, thus resulting in less space cooling load with reduced energy consumption. The overall finding concludes that the application of solar panel systems improves the energy efficiency of landed residences and helps reduce the carbon footprint in suburban areas. With proven energy-efficient performance, the application of the solar panel system in landed suburban residences can be considered as part of future guidelines towards reducing carbon footprint due to future urban sprawl.